2002
DOI: 10.1007/s00221-001-0990-8
|View full text |Cite
|
Sign up to set email alerts
|

Control of human locomotion under various task constraints

Abstract: The goal of this study was to identify the control mechanism used for locomotion pointing regulation under different external temporal constraints. Subjects ( n=8) had to walk on a treadmill through a number of virtual hallways and cross a pair of gliding doors that opened and closed at a constant preset frequency (0.5 Hz or 1 Hz). Crossing performance, step durations, and step lengths were used as dependent measures. The results revealed the regulation of locomotion occurred earlier and was more pronounced at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
14
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 5 publications
4
14
0
1
Order By: Relevance
“…The temporal constraints generated a specific functional behavior to control the regulation. Like those of Montagne et al (2002) and Buekers, Montagne, De Rugy, et al (1999), our results reveal the proportional relationship between the temporal constraints and the step at which regulation occurs. This relationship expresses the nature of perceptionmovement coupling.…”
Section: Speed Influence?mentioning
confidence: 53%
See 3 more Smart Citations
“…The temporal constraints generated a specific functional behavior to control the regulation. Like those of Montagne et al (2002) and Buekers, Montagne, De Rugy, et al (1999), our results reveal the proportional relationship between the temporal constraints and the step at which regulation occurs. This relationship expresses the nature of perceptionmovement coupling.…”
Section: Speed Influence?mentioning
confidence: 53%
“…It underlines the adaptation of the person-environment system and the systematic role played by temporal and spatial constraints. The task constraints play an important role: they define at a given step the initiation of regulation (e.g., Bradshaw & Sparrow, 2001;Montagne et al, 2002). In addition, they define the nature of regulation (Renshaw & Davids, 2004).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite the costs associated with erroneous motor decisions, several studies indicated that even adults might fail to leave a sufficient safety margin and attempt to fit their bodies through impossibly small apertures. For example, participants slightly misjudged their ability to pass through doorways without becoming wedged while walking normally (Gordon & Rosenblum, 2004; Warren & Whang, 1987), walking while carrying a horizontal pole (Wagman & Taylor, 2005), rolling in a wheelchair (Flascher, Shaw, Kader, & Aromin, 1995; Higuchi, Takada, Matsuura, & Imanaka, 2004), and walking on a treadmill through a virtual oscillating aperture projected on a screen (Buekers, Montagne, de Rugy, & Laurent, 1999; Montagne, Buekers, de Rugy, Camachon, & Laurent, 2002). Similarly, observers slightly misjudged their ability to pass under an overhead barrier with sufficient clearance to walk without banging their heads (Gordon & Rosenblum, 2004).…”
Section: Navigating Through Aperturesmentioning
confidence: 99%